Economic issues in silk cocoon production: a study at farm household, level in Southern India - S. Lakshmanan, (Journal of Agricultural Extension Management, 2025)
Mulberry sericulture helps to transform the economic livelihood of rural households in India. With the advent of new sericultural technologies, it has become popular due to higher cocoon productivity and lower cost of production (Lakshmanan el al., 1996, 1998, 2002, 2005). This enables the small and marginal farmers to use their limited land resources to cultivate mulbe1Ty more intensively under irrigated condition. More so, cost of inputs and cocoon price arc eventually subject to change with the demand and supply prospects. Therefore, data on cost of cocoon production and income profile from sericulture has to be studied periodically. Such information would help the farmers to take appropriate decisions on judicious investment in sc1iculture. Keeping in view the aforesaid aspects, the present study envisages understanding the cost of cocoon production and returns at the household level across different regions in Southern India